Influence of Infrared Radiation of Drying Characteristics, Total Phenolic Content, Antioxidant Capacity and Color Properties of Pomegranate Seeds - Doymaz, Ibrahim; Borucu, Elena; Kayacan-cakmakoglu, Selma; Sagdic, Osman (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2025)
The aim of this research is to analyze the drying behavior, antioxidant properties, total phenolic content (TPC), and color alterations of pomegranate seeds subjected to infrared drying at temperatures ranging from 55 degrees C to 75 degrees C. Analysis of the data revealed a decliningrate drying phase without evidence of a constant-rate phase. The drying rate and duration were found to be directly proportional to the infrared temperature applied; higher temperatures led to faster drying and reduced drying times. The drying process of pomegranate seeds in thin layers was investigated using twelve mathematical models. Among these models, the one presented by Aghbashlo et al. was determined to provide the most precise representation of the drying kinetics. The effective moisture diffusivity values varied between 8.76 x 10-10 and 1.96 x 10-9 m2/s, depending on the temperature range under consideration. Additionally, the activation energy was computed to be 59.37 kJ/mol. The range of TPC values in dry samples fluctuated from 6.19 to 8.20 mg gallic acid equivalent (GAE)/g of dry matter. The 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2 '-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and copper-reducing antioxidant capacity (CUPRAC) values varied between 5.57-6.13, 24.18-28.18, 10.33-17.59 TE/g dry matter, respectively. The range of Delta E values for the total color change fell between 3.96 and 9.19. Bioactive compound degradation in samples dried at high drying temperature (75 degrees C) is higher than in samples dried at 55 and 65 degrees C. When all the results were evaluated, it was determined that 55 degrees C was suitable for infrared drying of pomegranate seeds.
Keywords: activation energy; bioactive compounds; effective moisture diffusivity; mathematical modeling; pomegranate seeds; ENERGY-CONSUMPTION; KINETICS; ARILS; L.; MICROWAVE; DEGRADATION; QUALITY; AIR; Engineering